2019
DOI: 10.1007/s11676-019-00935-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early survival and growth of planted Scots pine (Pinus sylvestris) seedlings under extreme continental climate conditions of northern Mongolia

Abstract: Environmental factors play vital roles in successful plantation and cultivation of tree seedlings. This study focuses on problems associated with reforestation under extreme continental climatic conditions. The objectives were to assess relative seedling performance (survival and growth) with respect to plantation age, and to analyze the influence of specific climatic factors during the early stages of Scots pine (Pinus sylvestris L.) plantations. The study was carried out in reforested areas of the Tujyin Nar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Based on recent research, adapted silvicultural measures for climate-resilient forest management have been proposed. These include analysis and establishment of specific selective harvesting measures and the development of adjusted regeneration and planting concepts (Gradel 2017;Gerelbaatar et al 2019b). Some European studies, for example, have reported that thinning could be a measure for climate adaptation, since it has a positive impact on the amount of water available to the remaining trees (Gebhardt et al 2014, Olivar et al 2014).…”
Section: Lessons Learned Climate Effects On Trees and Climate-resiliementioning
confidence: 99%
See 3 more Smart Citations
“…Based on recent research, adapted silvicultural measures for climate-resilient forest management have been proposed. These include analysis and establishment of specific selective harvesting measures and the development of adjusted regeneration and planting concepts (Gradel 2017;Gerelbaatar et al 2019b). Some European studies, for example, have reported that thinning could be a measure for climate adaptation, since it has a positive impact on the amount of water available to the remaining trees (Gebhardt et al 2014, Olivar et al 2014).…”
Section: Lessons Learned Climate Effects On Trees and Climate-resiliementioning
confidence: 99%
“…The effect of timing of reforestation success has recently been scrutinized by Gerelbaatar et al (2019b), who found that the survival rate of seedlings in Scots pine plantations is a linear function of the number of dry days (days with air humidity below 30%) during the common planting period in May. The same authors elaborated threshold values of air humidity for the dieback of planted Scots pine seedlings in the Selenge Aimag.…”
Section: Timing Of Reforestationmentioning
confidence: 99%
See 2 more Smart Citations
“…Scots pine (Pinus sylvestris L.) is one of the most widely distributed tree species in Eurasia, and has a high commercial and ecological value (Xiao & Ceulemans, 2004). For Mongolia, pine forests play an important role in domestic timber production and forest ecosystem sustainability (Sukhbaatar et al, 2019). Currently, several studies were devoted to the development of allometric equations and predicting the AGB estimation for the main tree species of a given forest region (Danilin 2004;Chuluunbaatar, 2005;Battulga et al, 2013;Danilin & Tsogt, 2015;Dulamsuren et al, 2016;Dorjsuren et al, 2018;Altanzagas et al, 2019).…”
Section: Introductionmentioning
confidence: 99%